The Role of Transformational Leadership in Driving Educational Innovation - Fahyed, Fadhil Al; Syahreza, Dina Sarah; Malau, Grace Theresia; Hutauruk, Naomi; Juwita, Indah; Tarigan, Nimia Eliani Br (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
This study investigates transformational leaders who inspire and guide everyone in the educational community to commit to a common goal, provide clear direction, and create meaningful expectations for everyone. This research aims to develop a conceptual and comprehensive framework for how transformational leadership can influence and encourage change in educational innovation and related important concepts and obtain a comprehensive picture of how transformational leadership can influence and encourage change in educational innovation. The research method used in this journal is a literature review and descriptive method in which data is obtained from library sources, reading and taking notes to evaluate data obtained from the literature. Furthermore, the results of the review and analysis show that transformational leadership has a significant contribution in increasing innovation in the world of education. This study also explores the important role of transformational leaders in encouraging innovation through increasing innovation, technology support and commitment of organizational members.